Macroscopic Safety Requirements for Highly Automated Driving. Issue 3 (March 2019) - Junietz, Philipp; Steininger, Udo; Winner, Hermann
The common expectation for highly automated vehicles (HAVs) is that an introduction will lead to increased road safety and a reduction in traffic fatalities—at least in relation to the mileage. However, quantizing the safety requirements is still in discussion. This paper analyzes the risk acceptance in other fields and applies the safety level on today's traffic to derive references for acceptable risks. The focus is on macroscopic safety requirements, meaning accident rates per mileage, and not the behavior in individual driving situations. It was concluded that the acceptable risk varies according to the group involved and with the field share of automated vehicles. Increased safety of conventional driving in the future could lead to higher requirements as well. We also point out that it is not guaranteed that the given acceptable risk levels will also accepted by the user, because factors other than the accident statistics are relevant. However, as none of these risk levels can be proven before introduction, the monitoring of vehicles in the field is suggested. Despite increased research efforts in safety validation, uncertainty surrounding the safety of HAVs will remain at the time of introduction. Different introduction and risk management strategies are briefly introduced.